FREQUENCY OF VARIOUS HUMAN MALARIA INFECTIONS IN HOTTEST AREAS OF CENTRAL BALOCHISTAN,PAKISTAN: DUKI,HARNAI,AND SIBI: Various Human Malaria Infections in Central Balochistan - Yasinzai, Mohammad Iqbal; Kakarsulemankhel, Juma Khan (Pakistan Armed Forces Medical Journal, 2008)
Objective: This study was designed to assess the frequency of malaria infection in human population Duki, Harnai and Sibi the hottest areas of centre Balochistan, Pakistan. Study Design: A descriptive study. Place and duration of study: The study was conducted in Balochistan from July 2004 to June 2006. Patients and Methods: This study was conducted in Duki (8 localities), Harnai (7 localities) and Sibi (10 localities) and malarial parasites were identified in the blood slides of suspected patients from July, 2004 to June, 2006 and encompassed 6730 subjects. Results: Out of 6730 suspected cases of malaria, 2304 (34.2%) were found to be positive for malarial parasite in blood smear slides. Out of positive cases, 1316 (57.1%) were identified as Plasmodium falciparum infection, 988 (42.8%) cases with P. vivax. Seasonal variation was also noted in Duki area with highest (81.8%:36/44) infection of P. falciparum. in April and lowest (72.2%:26/36) infection in December. In Harnai area highest (84.2%:32/38) infection of P. falciparum in December and lowest (61.1%:11/18) infection in January. Similarly, in Sibi area highest (81.5%:31/38) infection of P. vivax in August and lowest (58.8%:30/51) infection in May. Infection with P. falciparum in male in Duki area was 62.5 % (10/16), 68.9% (60/87) in Harnai, 63.1% (24/38), infection with P. vivax in Sibi area, while in females 27.2% (6/22), 31.7% (13/41) and 21.4 % (36/168) respectively. There was no case of P. malaria and P. ovale infection observed in the present study. Conclusion: Human Malaria is quite frequent in the Duki, Harnai and Sibi, which were the hottest areas of Balochistan in Pakistan. In clinically suspected cases of malaria, there are very high slide positivity rate. Plasmodium falciparum is slightly more frequent. In Duki and Harnai, plasmodium falciparum is more frequent while in Sibi Plasmodium vivax was most frequent. This high frequency of Human malaria infection should be of great concern for authorities at malaria control programme in Pakistan.